Island community governance and coastal resource management - Pacete, Ofelia T; Sajo, Tomas A.; Hernando, Christine Mae D. (Iloilo City U.P. in the Visayas, College of Management, 2006)
The study focuses on strengthening the governance of island communities through a carefully planned intervention for the protection and conservation of coastal resources as mechanisms for achieving the goals of sustainable development. Particular attention is given to the assessment of the islands' natural resources in relation to development needs, crafting governance mechanisms for the development and management of coastal resources, harnessing the role of civil society organizations associated with managing coastal resources, designing co-management initiatives and collaborative partnership with stakeholders, and increasing the effectiveness level of promotion and enhancement of coastal resource management obtaining in the scattered island communities. By adopting a combination of descriptive and associative approaches in research, the study characterizes the natural resources obtaining in the islands and profiles the people living therein. It describes the existing practices of island governance and the condition of coastal resources. It investigates the relationships among barangay officials, household heads, and representatives of civil society as they participate in developing and managing coastal resources, solicit the involvement of civil society organizations, collaborate with various stakeholders in crafting co-management schemes, and promote coastal resource management to enhance the integrated development of the island communities. The results of the study are presented in the order of major areas of concerns as indicated in the specific objectives with corresponding hypotheses : 1) on the natural and physical resources of island communities; 2)On local government mechanisms for development and management of coastal resources; 3)On civil society/groups organizations and their roles in coastal resource management; 4) On co-management mechanisms facilitated in coastal resource management; 5) on promotion and enhancement of coastal resource management. Considering, the significant findings of the study, it is strongly recommended that the performance of the roles of civil society organizations must be clarified and strengthened so that their participation and involvement in the planning, implementation, and evaluation of various aspects of coastal resource management can be truly instrumental in achieving the goals of sustainable development for the welfare and benefit of the people in different island communities. To be more specific, the recommendations are centered on : 1)Functional involvement of civil society organizations, like NGOs and POs, in barangay governance as responsible members of different sectoral committees; 2)Development of mutually acceptable criteria for ensuring tangible results of CRMP operations; 3) formulation and design of effective strategies for solicitation of participation of civil society organizations in implementation of barangay-bases CRMP; 4) effective and persuasive endorsement of Memorandum of Agreement with civil society organizations in the barangay.
Research Paper
Keywords: Coastal resources management